Pro Asynchronous Programming with .NET - Blewett, Richard; Clymer, Andrew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Pro Asynchronous Programming with .NET teaches the essential skill of asynchronous programming in .NET. It answers critical questions in .NET application development, such as: how do I keep my program responding at all times to keep my users happy? how do I make the most of the available hardware? how can I improve performance? In the modern world, users expect more and more from their applications and devices, and multi-core hardware has the potential to provide it. But it takes carefully crafted code to turn that potential into responsive, scalable applications. With Pro Asynchronous Programming with .NET you will: Meet the underlying model for asynchrony on Windows$1 (Bthreads. Learn how to perform long blocking operations away from your UI thread to keep your UI responsive, then weave the results back in as seamlessly as possible. Master the async/await model of asynchrony in .NET, which makes asynchronous programming simpler and more achievable than ever before. Solve common problems in parallel programming with modern async techniques. Get under the hood of your asynchronous code with debugging techniques and insights from Visual Studio and beyond. In the past asynchronous programming was seen as an advanced skill. It$1 (Bs now a must for all modern developers. Pro Asynchronous Programming with .NET is your practical guide to using this important programming skill anywhere on the .NET platform.s
Keywords: Computer science; Computer Science; Computer Science, general